ASSESMENT OF BENEFITS AND CHALLENGES OF INTERNET MARKETING IN HOTELS IN THE TAMALE METROPOLIS - Denteh, S. N.; Ahiekpor, P. A.; Nketia, A. (UDS International Journal of Development, 2019)
The purpose of the study was to determine internet usage in some selected hotels in the Tamale metropolis. To achieve this purpose, data was collected from guests visiting the facility and management of the hotels during the period of the study with the use of questionnaire. A sample size of 80 respondents was obtained comprising 60 guests. A further 20, comprising of management of the various facilities were also contacted. The analyzed data was represented using bar charts, pie charts and tables. The study revealed that most of the hotels had internet devices and employs the internet as part of their marketing strategies. Another finding of the study was that hotels prefer word of mouth marketing to traditional and internet marketing. The hotels that employ internet services as part of their marketing strategy enjoy some benefits such as large customer outreach, customer satisfaction and improved communication with some challenges such as high cost in purchasing internet equipment and limited penetration of internet usage among domestic customers. The study therefore suggest that the hospitality industry should encourage the use of internet marketing in their facilities for the improvement of business performance as well as recruiting staff with ICT background in order to deliver quality service. Keywords: Internet, Marketing Strategy, Internet Marketing, Internet Equipment, Customer Satisfaction.